Peran Perawatan Diri sebagai Mediator antara Efikasi Diri dan Kualitas Hidup pada Pasien GERD (Gastroesophageal Reflux Disease) - Sulistyarini, Raden; Susanti, Devi Rika; Alfairuz, Hafiz (Jurnal Online Psikogenesis, 2024)
GERD is a chronic condition that can reduce the quality of life of patients, especially if not managed properly. Two important factors that affect the quality of life in GERD patients are self-efficacy and self-care, but how self-efficacy affects the quality of life through self-care mechanisms still requires a deeper understanding. Objective: This study aims to determine the role of self-care as a mediator between self-efficacy and quality of life in GERD (Gastroesophageal Reflux Disease) patients. Method: The subjects in this study were 152 subjects consisting of 24 men and 128 women aged over 18 years and had been diagnosed with GERD by a doctor at least 6 months after receiving the diagnosis. This study uses a quantitative approach, the relationship model in this study is three variables analyzed by mediation analysis. Data collection was carried out using the World Health Organization Quality of Life (WHOQOL-BREF) scale, Generalized Self-Efficacy Scale (GSES) and Denyes Self Care Agency Instrument (DSCAI-90). The analysis in this study used the help of the JASP statistical application version 0.18.3.0. Results: Self-efficacy has an indirect effect on quality of life (indirect effect = 0.271, 95% CI = [0.128, 0.415]) p <0.01) through self-care as a mediator. The implications of this study are that it can help health workers to evaluate factors that influence the quality of life of GERD patients. Furthermore, the results of this study can provide various alternative treatments that are right for GERD patients by considering efficacy and self-care as factors that play a role in improving the quality of life in GERD patients. Keywords: Self-Efficacy, Quality of Life, Self-Care, GERD Patients Keywords: Self-Efficacy, Quality of Life, Self-Care, GERD Patients